2011
DOI: 10.1017/s0714980811000110
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Old as a ‘Pharmaceutical Person’: Negotiation of Health and Medicines among Ethnoculturally Diverse Older Adults

Abstract: Because medication prescribing and use have become a normative aspect of health care for older adults, we seek to understand how individuals navigate prescribed-medication use within the context of aging. We reasoned that, for those who are ambulatory, medication use is likely influenced by ethnocultural meanings of health and experiences with alternative approaches to health care. Accordingly, we conducted a qualitative study, with in-depth interviews, on a diverse sample of older adults in order to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 55 publications
(64 reference statements)
0
33
0
Order By: Relevance
“…Lai and Kalyniak's [ 33 ] study of predictors related to accessing annual physical examinations among older Chinese immigrants revealed that, in addition to lack of knowledge about healthcare coverage and service availability, the low rates of accessing healthcare could be related to a lack of understanding about the importance and benefits of preventive annual physical examinations. Ballantyne et al [ 34 ] investigated medication use among a diverse group of older immigrants and found that older immigrants from China, Hong Kong, Vietnam, and Portugal often avoided discussing their self-care and alternative healthcare practices with their physicians; they also found that the participants often disagreed with the assessment and the recommended treatment and sought out and tried alternative treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Lai and Kalyniak's [ 33 ] study of predictors related to accessing annual physical examinations among older Chinese immigrants revealed that, in addition to lack of knowledge about healthcare coverage and service availability, the low rates of accessing healthcare could be related to a lack of understanding about the importance and benefits of preventive annual physical examinations. Ballantyne et al [ 34 ] investigated medication use among a diverse group of older immigrants and found that older immigrants from China, Hong Kong, Vietnam, and Portugal often avoided discussing their self-care and alternative healthcare practices with their physicians; they also found that the participants often disagreed with the assessment and the recommended treatment and sought out and tried alternative treatments.…”
Section: Resultsmentioning
confidence: 99%
“…As active, reflective consumers and ‘expert patients’, members of the public evaluate and have the potential to accept, challenge or resist the profession’s claims about the value of medicines [2,21]. People’s beliefs about medicines, their direct or vicarious experiences of them, their attention to or knowledge of documented side effects and risks associated with specific medicines—all influence their interests in and alignment with medical opinion or an individual physician’s medication recommendations [13,36]. In addition, physicians have been shown to respond to patients’ medication expectations or demands for a prescription, even if these contradict the physician’s intended actions [37] (Figure 1h).…”
Section: The Field Of Medications and Its Agentsmentioning
confidence: 99%
“…, non-adherent) patient’ [69]. Research on lay-perspectives on medicines has come to show users to be thoughtful, considered agents of medicine use and consumption, who take responsibility for medication decisions about the suitability of medicines for specific conditions and contexts [13,17,70,71,72,73,74,75,76,77,78] (Figure 1h).…”
Section: The Field Of Medications and Its Agentsmentioning
confidence: 99%
See 2 more Smart Citations